THE PERCEPTION TOWARDS TRANSITION TO IFRS CONVERGENCE IN INDIA AND ITS BENEFITS - Seethalekshmy.C; Juji George; Misheal Tomy; Neethu Anil (International Journal of Psychosocial Rehabilitation, 2020)
Convergence with International Accounting Standards as issued by the International Accounting Standard Board (IASB) is receiving its due importance over a period of time. Consistent, comparable and understandable financial statements are the necessity of every companies as well as the need of all the users of the same. Now a day, companies are expecting and receiving investments from across the world. A uniform accounting standard to be maintained in the preparation of financial statements are necessary for the corporate, for the easy understandability and comparability for their global investors. Therefore, both corporate officials and professionals have similar concern in implementing IFRS. Both groups agreed on the importance and usefulness of globally harmonizing the accounting standards. On this site, India joined this band wagon and MCA in consultation with the Institute of Chartered Accountants of India (ICAI) has decided to converge with IFRS. The Council of ICAI, at its 259th meeting, held in May, 2006, expressed the view that the IFRSs may be adopted in totality at least for listed and large corporate entities keeping in view the expected advantages in saving of cost of capital for India entities raising capital abroad, saving in cost for such entities for nit preparing set if financial statements as well as for increasing opportunities for Indian professionals abroad. Paper explores the responses towards the perception of the professional towards the implementation and the features of the IFRS Convergence. The present study also focussed on evaluating the benefits to both companies and investors on the transition to IFRS Convergence